Implementation of Article 87 Law Number 2 of 2004 Concerning Resolution of Industrial Relations in the Court of Industrial Relations in Article of the Republic of Indonesia - Setia Permana; T. Subarsyah; Evita Firdatunnisa (GoAcademica Research & Publishing, 2020)
The formulation of article 87 of Law Number 2 of 2004 in its implementation still requires firmness to provide certainty that what is meant by trade unions / labor unions that can become legal counsel to proceed at the Industrial Relations Court to represent their members are trade unions / labor unions located in in the company or including labor unions / labor unions outside the company. The purpose of this study is to describe / describe the rights and authority of trade unions / labor unions as legal counsel in the process of resolving industrial relations disputes along with descriptions (describing) the legal consequences related to the rights and authority of trade unions / labor unions .The type of research used is normative law which is intended to examine the provisions of positive law. The method of approach used in this study is the approach: normative law, which examines the legal norms that apply, both in the form of laws, implementing regulations and other regulations that have links with the issues discussed in the study. Settlement of industrial relations disputes can be done through resolutions outside the Industrial Relations Court (Non-Litigation) and in the Industrial Relations Court (Ligitation). Implementation of Article 87 of Law No. 2 of 2004 concerning Settlement of Industrial Relations Disputes, in the Decision of the Supreme Court of the Republic of Indonesia Number 933K / PDT.SUS / 2009 dated May 5, 2010 and Number 488K / PDT.SUS / 2012 dated October 22, 2012, referred to as trade unions / labor unions has a legal standing representing its members proceeding in the Industrial Relations Court is a trade union / labor union both inside and outside the company.